Spectroscopic Study of the Forbidden Lines [OIII] and [SII] of Crab Nebula Supernova Remnant - Ali, Lana (Iraqi Journal of Science, 2025)
As a star explode as a supernova its ejecta will directly interact with relatively low density interstellar medium with high shock wave velocity, and due to this interaction many of forbidden emission lines will give a raise from both the excitation and ionization of the atom in the region. So, the study of these emission lines can reveal many physical properties of the region, in this case the remnant of the supernova, such as temperature, density, composition, and many other important physical processes. In this paper the optical spectrum of the young galactic supernova remnant which is the Crab Nebula has used, in order to calculate it’s electron temperature (Te) and electron density (ne) by using the [OIII] and [SII] forbidden lines. From the obtained results it’s found that, the remnant has Te reach to 17,000 500°K that raises from high shock velocity according to the intensity ratio of which is found to be , although the remnant has such high Te and high shock velocity it’s found that, only about 64% of pre-shock helium is fully pre-ionized in the remnant. In addition to that when the intensity ratio of both [ ] and [SII] lines has taken it’s found that, the remnant is an intermediate density remnant which has ne equal to 1300 10 cm-3.